Prevalence of prediabetes and diabetes vary by ethnicity among U.S. Asian adults at healthy weight, overweight, and obesity ranges: an electronic health record study - William S. Vicks; Joan C. Lo; Lynn Guo; Jamal S. Rana; Sherry Zhang; Nirmala D. Ramalingam; Nancy P. Gordon (BMC, 2022)
Abstract Background Asian adults develop Type 2 diabetes at a lower body mass index (BMI) compared to other racial/ethnic groups. We examined the variation in prevalence of prediabetes and diabetes among Asian ethnic groups within weight strata by comparing middle-aged Chinese, Filipino, South Asian, and White adults receiving care in the same integrated healthcare delivery system. Methods Our retrospective cross-sectional U.S. study examined data from 283,110 (non-Hispanic) White, 33,263 Chinese, 38,766 Filipino, and 17,959 South Asian adults aged 45-64 years who were members of a Northern California health plan in 2016 and had measured height and weight. Prediabetes and diabetes were classified based on laboratory data, clinical diagnoses, or diabetes pharmacotherapy. Age-standardized prevalence of prediabetes and diabetes were compared by race/ethnicity within healthy weight, overweight, and obesity categories, using standard BMI thresholds for White adults (18.5 to < 25, 25 to < 30, ≥ 30 kg/m2) and lower BMI thresholds for Asian adults (18.5 to < 23, 23 to < 27.5, ≥ 27.5 kg/m2). Prevalence ratios (PRs) were used to compare the prevalence of diabetes and prediabetes for Asian groups to White adults in each weight category, adjusted for age and BMI. Results Across all weight categories, diabetes prevalence was higher for Asian than White adults, and among Asian groups it was highest for Filipino and South Asian adults. Compared to White, PRs for South Asian men/women at healthy BMI were 1.8/2.8 for prediabetes and 5.9/8.0 for diabetes, respectively. The PRs for Filipino men/women at healthy BMI were 1.8/2.6 for prediabetes and 5.0/7.5 for diabetes, respectively. For Chinese men/women at healthy BMI, the PRs for prediabetes (2.1/2.9) were similar to Filipino and South Asian, but the PRs for diabetes were lower (2.1/3.4). Conclusion Chinese, Filipino, and South Asian adults have higher prevalence of prediabetes and diabetes than White adults in all weight categories, despite using lower BMI thresholds for weight classification in Asian groups. Within Asian ethnic groups, Filipino and South Asian adults had considerably higher diabetes prevalence than Chinese adults. Our data emphasize the disproportionate metabolic risk among middle-aged Asian adults and underscore the need for diabetes screening among high-risk Asian groups at healthy BMI levels.